Study of enteric fever and malaria incidence in southern part of Nepal - Rai, D.R.; Kshetry, N.T.; Tamang, M.D.; Pokhrel, B.M. (Journal of Institute of Medicine Nepal, 2007)
This study was done in order to present the incidence of enteric fever and malaria among patients with febrile illness which can play significant role in nation’s disease control & prevention efforts. Conventional method of Widal test and Blood culture were done for diagnosis of enteric fever and Kirby Bauer disc diffusion method was applied to find antibiotic sensitivity pattern of the isolate. Thin smear method was performed to detect the malarial parasites. A total of 611 cases attended at hospital complaining febrile illness and 150 people without any symptoms of fever were the subject of study. Among 611, 29.8% (182/611) were found positive with significant titre. Infection rate was found similar between sexes, however, more than 70%incidence were clustered among the age group 11-40 year. No significant difference of Hb was found among positive and negative cases, however, number of neutrophil and TLC was remarkably high among positive cases. Among 60 cases subjected to blood culture 16.7% (10/60) were proven culture positive for Salmonella spp. with predominant S. typhi. Ciprofloxacin and Ceftriaxone were found promising drugs. Seasonally mid May/April was found peak period of incidence. Among 150 people without any symptoms of fever 28 (18.7%) showed agglutination positive with low titre. As 50% of H & whole O antibody showed the titre of 1:80 & 1:40, local titre value against H & O antigen is 80 and 40, respectively. Malarial parasite detection rate was 3.6% (6/166) with ratio of P. vivax & P. falciparum 2:1. This finding provide current situation of incidence of malaria and enteric fever with antibiotic susceptibility pattern which enable the physician to tackle the cases very effectively. Journal of Institute of Medicine Vol.27(3) 2005